Discovering Cyber Terrorism Using Trace Pattern - Nurhashikin, Mohd Salleh; Siti Rahayu, Selamat; Robiah, Yusof; Shahrin, Sahib (IJNS, 2016)
Nowadays, as the Internet user increased, the number of cyber threats is also increased. Internet has provided a medium for criminal to do the crime and become the target for cyber terrorist to spread their negative propaganda, and promote extreme activities. One of the crimes is cyber terrorism. Cyber terrorism became more sophisticated and it difficult to discover its activities. Hence, this paper proposes tracing technique for discovering cyber terrorism based on trace pattern. Trace pattern will represent the behavior and activities of cyber terrorism. Cyber terrorist's website is used as the datasets. Using tracing technique, cyber terrorist's activities are identified by extraction and classifying the traces to the keyword that is usually used by the terrorist. Then, the traces will be linked with the cyber terrorism components in order to identify the relationship between them. Using trace pattern, the verification process will be conducted to verify the traces in order to identify the cyber terrorism activities and potential terrorist. This trace pattern can be used in facilitating the forensic investigation process in discovering cyber terrorism activities.